Self-DNA at the Epicenter of SLE: Immunogenic Forms, Regulation, and Effects - Soni, Chetna; Reizis, Boris (Frontiers in Immunology, 2019)
Self-reactive B cells generated through V(D)J recombination in the bone marrow or through accrual of random mutations in secondary lymphoid tissues are mostly purged or edited to prevent autoimmunity. Yet, 10–20% of all mature naïve B cells in healthy individuals have self-reactive B cell receptors (BCRs). In patients with serologically active systemic lupus erythematosus (SLE) the percentage increases up to 50%, with significant self-DNA reactivity that correlates with disease severity. Endogenous or self-DNA has emerged as a potent antigen in several autoimmune disorders, particularly in SLE. However, the mechanism(s) regulating or preventing anti-DNA antibody production remain elusive. It is likely that in healthy subjects, DNA-reactive B cells avoid activation due to the unavailability of endogenous DNA, which is efficiently degraded through efferocytosis and various DNA-processing proteins. Genetic defects, physiological, and/or pathological conditions can override these protective checkpoints, leading to autoimmunity. Plausibly, increased availability of immunogenic self-DNA may be the key initiating event in the loss of tolerance of otherwise quiescent DNA-reactive B cells. Indeed, mutations impairing apoptotic cell clearance pathways and nucleic acid metabolism-associated genes like DNases, RNases, and their sensors are known to cause autoimmune disorders including SLE. Here we review the literature supporting the idea that increased availability of DNA as an immunogen or adjuvant, or both, may cause the production of pathogenic anti-DNA antibodies and subsequent manifestations of clinical disease such as SLE. We discuss the main cellular players involved in anti-DNA responses; the physical forms and sources of immunogenic DNA in autoimmunity; the DNA-protein complexes that render DNA immunogenic; the regulation of DNA availability by intracellular and extracellular DNases and the autoimmune pathologies associated with their dysfunction; the cytosolic and endosomal sensors of immunogenic DNA; and the cytokines such as interferons that drive auto-inflammatory and autoimmune pathways leading to clinical disease. We propose that prevention of DNA availability by aiding extracellular DNase activity could be a viable therapeutic modality in controlling SLE.